Chronic lateral ankle instability using anterior tibiofibular ligament distal fascicle transfer augmentation repair: an anatomical, biomechanical, and histological study - Wang, Ruihan; Yang, Yingqiu; You, Guixuan; Huang, Lei; Zhou, Xin; Jiang, Songtao; Shi, Houyin; Wang, Guoyou; Zhang, Lei (Frontiers in Bioengineering and Biotechnology, 2024)
The transfer of the anterior tibiofibular ligament distal fascicle (ATiFL-DF) for the augmentation repair of the anterior talofibular ligament (ATFL) shows potential as a surgical technique. However, evidences on the benefits and disadvantages of this method in relation to ankle joint function are lacking.Purpose: This study aimed to provide comprehensive experimental data to validate the feasibility of ATiFL-DF transfer augmentation repair of the ATFL.Methods: This study included 50 embalmed ankle specimens to measure various morphological features, such as length, width, thickness, and angle, for evaluating similarities between the ATiFL-DF and ATFL. Furthermore, 24 fresh-frozen ankle specimens were examined for biomechanical testing of the ATiFL-DF transfer augmented repair of the ATFL. Finally, 12 pairs of ATiFL-DF and ATFL tissues from fresh-frozen ankle specimens were treated with gold chloride staining to analyze mechanoreceptor densities.Results: Anatomical studies found that the lengths and thicknesses of the ATFL and ATiFL-DF are similar. Biomechanical outcomes showed that performing ATiFL-DF transfer for ATFL repair can improve the stability of the talus and ankle joints. This is evident from the results of the anterior drawer, axial load, and ultimate failure load tests.However, performing ATiFL-DF transfer may compromise the stability of the distal tibiofibular joint, based on the Cotton and axial load tests at an external rotation of 5°.Analysis of the histological findings revealed that mechanoreceptor densities for four types of mechanoreceptors were comparable between the ATiFL-DF and ATFL groups.Conclusions: ATiFL-DF transfer is a viable method for augmenting ATFL repair. This technique helps to improve the stability of the talus and ankle joints while compensating for proprioception loss. Although ATiFL-DF transfer augmented repair of the ATFL may negatively affect the stability of the distal tibiofibular joint, this procedure can enhance the stability of the talus and ankle joints.